Studies into the development of novel tandem reactions aimed at the construction of complex polycyclic structures - Clement, Roxanne (University of Ottawa (Canada), 2005)
The scope and limitations of the tandem oxy-Cope/Claisen/ene/Claisen and the oxy-Cope/Claisen/ene reactions were investigated through the synthesis of various substrates possessing both allyl and propargyl moieties on the tertiary hydroxyl group. Substrates 1 and 2 led to degradation or the isolation of complex mixtures, indicating that the tandem pericyclic sequences were very sensitive to functionality. The 1,3-enynes 3 were found to undergo an intramolecular [4+2] cycloaddition in place of the expected oxy-Cope/Claisen/ene rearrangement, thus generating aromatic compounds 4.* The tandem oxy-Cope/Claisen/ene/HDDA reaction was developed over the course of this research. Microwave irradiation of propargyl ethers 5 provided the diene intermediates 6 via a tandem oxy-Cope/Claisen/ene reaction. The corresponding magnesium alkoxides of 6, generated in situ by treatment with a solution of MgBr2-OEt2/base, reacted upon the addition of various dienophiles to afford the diterpenes 7 as sole diastereoisomers [dr > 25:1]. The scope and limitations of this reaction were investigated through the preparation of various derivatives.* *Please refer to dissertation for diagrams.
Keywords: Chemistry, Physical.